2016
DOI: 10.1097/mib.0000000000000763
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Predictors of High Healthcare Use in Patients with Inflammatory Bowel Disease

Abstract: Background Inflammatory bowel disease (IBD) is a heterogeneous chronic inflammatory condition requiring significant healthcare expenditure. Subgroups of individuals contribute disproportionately to spending. We aimed to determine demographic and clinical factors predictive of high healthcare expenditures for IBD patients followed over a multiyear period. Methods This was a registry analysis using a prospective observational, consented, natural history registry from a tertiary IBD center and associated medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…1719 In addition, anxiety has been associated with worse outcomes among pediatric patients with IBD 20 and increased resource utilization among adult patients with IBD. 21,22 Although the impact of these psychological comorbidities has been evaluated in multiple studies, a majority of patients with UC or CD may not receive adequate psychosocial support in the scheme of their overall treatment for IBD. 23 Among patients with CD in our population, a co-existing diagnosis of anxiety or depression was associated with readmission within 90 days in both the unadjusted analysis and adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…1719 In addition, anxiety has been associated with worse outcomes among pediatric patients with IBD 20 and increased resource utilization among adult patients with IBD. 21,22 Although the impact of these psychological comorbidities has been evaluated in multiple studies, a majority of patients with UC or CD may not receive adequate psychosocial support in the scheme of their overall treatment for IBD. 23 Among patients with CD in our population, a co-existing diagnosis of anxiety or depression was associated with readmission within 90 days in both the unadjusted analysis and adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In our prior five year analysis of 1600 patients with IBD, 54.8% (n=876) of whom had CD, a subset of 9% of patients were found to account for 51.2% of the five year cumulative financial charges for the entire cohort. (17) With the rising cost of healthcare in the US, there is now a mounting interest to identify these high utilizers so that interventions to improve co-ordination of care and preventive care for them maybe tailored and better enforced. (23)…”
Section: Discussionmentioning
confidence: 99%
“…(14-16) In our previous study additional factors such as black race, use of opiates, penetrating CD phenotype and the use of more aggressive medical therapy at first visit were baseline characteristics that showed association with increased healthcare utilization and expenditure over the next five years. (17) Given the ability of change in LI to delineate distinct CD phenotypes, we aimed to characterize the financial burden from all medical care in a 5-year prospective cohort of CD patients stratified into LI-based disease phenotypes and to evaluate its utility in identifying the subset of costliest patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that black patients are suspected to have an overall lower prevalence of IBD in the US, prior studies have suggested that black patients are more likely to experience IBD-related hospitalizations and higher IBD-related mortality when compared to non-Hispanic white and Hispanic populations. 2 Additionally, although black race has been associated with an increased likelihood of significant healthcare expenditures related to IBD, 3 in other evaluations, black patients were less likely to receive therapy with infliximab 4 and thiopurines 5 when compared to white patients. Similarly, Hispanic patients are less likely to receive therapy with biologics and immunomodulators when compared to white patients.…”
Section: Introductionmentioning
confidence: 92%